A Comprehensive Review of Existing Risk Assessment Models in Cloud Computing - Amini A.; Jamil N. (Institute of Physics Publishing, 2023)
Big data; Cloud computing; Security of data; Ubiquitous computing; Assessment mechanism; Cloud computing environments; Management efforts; Qualitative risk assessment; Risk assessment models; Risk assessment